2014
DOI: 10.7862/rb.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of removal organic and biogenic compounds in hydrophyte bioreactor using biopreparation

Abstract: Stosowanie biopreparatów w oczyszczalniach ścieków wpływa na optymalizację rozkładu zanieczyszczeń organicznych w ściekach (odchody, papier, resztki roślinne, tłuszcz), lepszą biodegradację środków piorących i myjących, a także eliminację przykrych zapachów. Celem badań opisanych w artykule była intensyfikacja pracy oczyszczalni hydrofitowej z wykorzystaniem biopreparatu, którego głównym składnikiem jest biohumus. Uzyskane wyniki potwierdziły wpływ dawkowanych substancji humusowych na wzrost efektywności usuwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Rashed, E.M., & Massoud, M. (2015) showed that using eff ective microorganisms activated with molasses in activated sludge technology proved to be successful as an enhanced biological phosphorus removal. However, the use of biopreparation in the hydrophyte bioreactor contributed to the increase in phosphorus elimination by 11% (Warężak et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rashed, E.M., & Massoud, M. (2015) showed that using eff ective microorganisms activated with molasses in activated sludge technology proved to be successful as an enhanced biological phosphorus removal. However, the use of biopreparation in the hydrophyte bioreactor contributed to the increase in phosphorus elimination by 11% (Warężak et al 2014).…”
Section: Discussionmentioning
confidence: 99%